The Relationship of Supplementary Feeding, Breast Milk (MP-ASI) to Infants with The Event of Diarrhea - Reni Anggraeni; Musheer Abdulwahid Abdo Aljaberi; Nisha Nisha Nambiar; Tukimin Bin Sansuwito; Nenden Lesmana Wati (Qualitative and Quantitative Research Center, 2022)
Diarrhea is one of the causes of death in toddlers, and one of the factors that causes diarrhea is MP-ASI. Based on the most significant proportion of diarrhea sufferers at the Baros Health Center in the last three months of October, November, and December 2021, 87 infants aged 0-12 months and 29 infants aged 12-24 months, respectively, and 31 infants aged 25-60 months. This research aims to determine the relationship between complementary feeding and the incidence of diarrhea in infants aged 3-12 months in the Baros Public Health Center, Sukabumi City, Indonesia. This research used a cross-sectional population, and the total sampling was 48 infants aged 3-12 months. The analysis of data used Chi-Square. The inappropriate provision of complementary feeding to infants aged 3-12 months, 26 respondents (54.2%), and the appropriate ones were 22 respondents (45.8 %), the incidence of diarrhea in infants aged 3-12 months who had diarrhea as many as 28 respondents (58.6%) and who did not have diarrhea as many as 20 respondents (41.7%). The result shows a relationship between giving complementary feeding to infants aged 3-12 months and the incidence of diarrhea with a value of 0.00 (<0.05). There is a relationship between the provision of complementary foods for breast milk (MP-ASI) and the incidence of diarrhea in infants aged 3-12 months. Giving MP-ASI is one of the essential needs, but what needs to be considered by the mother is the appropriate age of the baby. Providing information related to MP-ASI knowledge to mothers is the key to preventing diarrhea in infants.